2021
DOI: 10.14718/acp.2021.24.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de autorregulación de la motivación de estudiantes universitarios y su relación con el ambiente de clase en asignaturas de matemáticas

Abstract: El presente estudio tuvo como objetivos identificar las estrategias de autorregulación de la motivación utilizadas por estudiantes universitarios en las asignaturas de matemáticas, así como examinar las relaciones entre sus creencias motivacionales y las estrategias de autorregulación de la motivación utilizadas, y explorar la relación entre las estrategias de autorregulación de la motivación y su percepción sobre aspectos del ambiente de clase. Para esto, se utilizó una muestra de 224 estudiantes universitari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The reasons for this decline may lie precisely in the change in teaching: classes were no longer face-to-face, reducing interactions among classmates and between students and teachers, and relegating virtual classrooms in universities, videoconferencing applications and e-mail as the only spaces for telematic interaction. In this sense, several studies have addressed how increased peer interaction, teacher-student interaction, and a positive and safe climate [37][38][39][40] improved levels of SRM.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this decline may lie precisely in the change in teaching: classes were no longer face-to-face, reducing interactions among classmates and between students and teachers, and relegating virtual classrooms in universities, videoconferencing applications and e-mail as the only spaces for telematic interaction. In this sense, several studies have addressed how increased peer interaction, teacher-student interaction, and a positive and safe climate [37][38][39][40] improved levels of SRM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is essential to promote selfregulatory strategies and their effective use in different areas (Ospina and Serrano, 2021). These are based, in turn, on metacognitive strategies, resource control, management strategies, and motivational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al, 2022). It has been identified that aspects of the classroom environment, such as support offered by the teacher, have a strong relationship with the self-regulatory motivational strategies used by students (Rojas-Ospina & Valencia-Serrano, 2021). Consequently, the support of teachers is an essential factor in the interaction between students and teachers.…”
Section: Methodsmentioning
confidence: 99%
“…In students who learn face-toface, teachers' affective factors such as immediacy, supportiveness, inclusiveness, being warm and caring, and their friendships with the students play a greater role in developing students' course knowledge and skills (W. Zheng et al, 2022). It has been identified that aspects of the classroom environment, such as support offered by the teacher, have a strong relationship with the self-regulatory motivational strategies used by students (Rojas-Ospina & Valencia-Serrano, 2021). Consequently, the support of teachers is an essential factor in the interaction between students and teachers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%